Studying the adaptogenic activity of a series of tetrahydropyrido[2,1-b] [1,3,5] thiadiazine derivatives - E. Yu. Bibik; I. A. Nekrasa; A. V. Demenko; K. A. Frolov; V. V. Dotsenko; S. G. Krivokolysko (Бюллетень сибирской медицины)
Introduction. In the modern world people are exposed to the influence of adverse psychological and physical factors, escalating in intensity. The search for new pharmacodynamic effects of [1,3,5]-thiadiazine derivatives designated by significant biological activity of these compounds is an essential issue.Aim. To research adaptogenic activity of tetrahydropyrido[2,1-b][1,3,5]thiadiazine derivatives using a modified Porsolt Forced Swim Test.Materials and methods. Four substances from the group of 3-R-8-aryl-6-oxo-3,4,7,8-tetrahydro-2H,6Hpyrido[2,1-b][1,3,5]thiadiazine-9-carbonitriles were selected for the research. Rats were divided into a control group, 5 reference groups (amitriptyline, caffeine, thiotriazolin, thiocetam, ginseng) and 4 experimental groups according to the number of the studied original tetrahydropyrido[2,1-b][1,3,5] thiadiazine derivatives.Results. Intragastric injection of substance 2 for 5 days in the modified forced swim test (forced swimming with freight) increased work capacity and endurance of the rats by 103.42% as opposed to the initial results. The detected adaptogenic activity of this tetrahydropyrido[2,1-b][1,3,5]thiadiazine derivative six times exceeds adaptogenic activity of ginseng and seven times that of amitriptyline. The rats in the control group were active for a bit longer time. Ginseng raised the time of activity by 17% at day 5. Caffeine essentially reduced work capacity and endurance. Amitriptyline showed adaptogenic activity at day 3 of the research (increase by 10.4%). Thiotriazolin also showed adaptogenic activity on day 3 of the research (increase by 30.17%). Thiocetam increased the time of activity by 78.55%. Substance 4 had adaptogenic activity too; it increased the time of activity in aversive conditions by 58.25%, which three times exceeds this parameter for ginseng and four times for amitriptyline.